2009
DOI: 10.1128/aem.00040-09
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Biogeography of Six Salt Lakes in Inner Mongolia, China, and a Salt Lake in Argentina

Abstract: We used cultivation-independent methods to investigate the prokaryotic biogeography of the water column in six salt lakes in Inner Mongolia, China, and a salt lake in Argentina. These lakes had different salt compositions and pH values and were at variable geographic distances, on both local and intercontinental scales, which allowed us to explore the microbial community composition within the context of both contemporary environmental conditions and geographic distance. Fourteen 16S rRNA gene clone libraries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
64
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 64 publications
12
64
1
7
Order By: Relevance
“…This study revealed that fungal community composition was positively correlated with geographic distance, and that geographic distance was a driver of diversity (r ¼ 0.224, P ¼ 0.003) at a large scale in wetlands. The effect of geographic distance on fungal biogeography in this study was consistent with results for bacterial biogeography in sediments (Pagaling et al, 2009;Schauer et al, 2010) and for the biogeography of macroorganisms in wetlands (Declerck et al, 2011). That the distributions of larger organisms are limited by mountains, large bodies of water and other physical barriers seems reasonable (Prosser et al, 2007).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This study revealed that fungal community composition was positively correlated with geographic distance, and that geographic distance was a driver of diversity (r ¼ 0.224, P ¼ 0.003) at a large scale in wetlands. The effect of geographic distance on fungal biogeography in this study was consistent with results for bacterial biogeography in sediments (Pagaling et al, 2009;Schauer et al, 2010) and for the biogeography of macroorganisms in wetlands (Declerck et al, 2011). That the distributions of larger organisms are limited by mountains, large bodies of water and other physical barriers seems reasonable (Prosser et al, 2007).…”
Section: Discussionsupporting
confidence: 78%
“…Recent studies have shown that the drivers of fungal and bacterial diversity differ with scale and microorganism type (Fierer et al, 2007;Pommier et al, 2007;Ge et al, 2008;Pagaling et al, 2009). MRT analysis in this study showed that the distribution of fungi in sediments along the Changjiang River and in other samples across China was significantly influenced by historical contingencies (sampling location).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Although the share of new sequences in the bacterial library (42.3%) was less than that in the archaeal one (53.9%) [10], the degree of novelty concerning the higher taxonomic level and sequences with similarity of less than 90% to the closest match and 85% to the culturable neighbour were established. Bacterial diversity on the level of higher taxa could be explained by the reported observation that halophilic bacteria are less mobile or less robust across large distances than halophilic archaea and show a higher tendency towards endemism [36]. Sequences with similarity of less than 90% to the closest match and 85% to the culturable neighbour were established.…”
Section: Degree Of Novelty Of Ps Bacterial Sequencesmentioning
confidence: 99%
“…Achieving this goal requires coordinated, detailed, accurate measurements of both physical and biological factors, but obtaining this information over temporal and spatial scales relevant to natural microbial communities is challenging. Extreme hypersaline aqueous environments harboring limited phylogenetic diversity provide tractable model ecosystems to confront these challenges (Demergasso et al, 2008;Bodaker et al, 2009;Pagaling et al, 2009;Oh et al, 2010;Boujelben et al, 2012;MakhdoumiKakhki et al, 2012;Oren, 2013). Although overall salt concentrations in these habitats are, by definition, at or exceeding the limits of ionic solubility, geochemical variation in water sources as well as minerals dissolved from surrounding rocks and sediments contribute to variable ratios of different ionic species over space and time (Javor, 1989;Oren, 2013).…”
Section: Introductionmentioning
confidence: 99%